2005
DOI: 10.1158/1541-7786.mcr-05-0144
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Invasive Mouse Skin Carcinomas in Transgenic Mice with Mutations in Both H-ras and p53

Abstract: Synergistic interaction between H-ras and p53 were systematically examined during skin tumorigenesis. Concurrent expression of an activated H-ras gene and a mutant p53 gene was accomplished by crossing p53 Val135/wt mice with TGÁAC mice. Topical application to wild-type mice with benzo(a)pyrene (BaP) alone produced f26% skin tumor incidence, whereas BaP treatment of p53 wt/wt Hras TGÁAC/wt , p53 Val135/wt Hras wt/wt , and p53 Val135/wt Hras TGÁAC/wt mice produced a 75%, 77%, and 100% incidence of skin tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
11
1
1
Order By: Relevance
“…When both CDKN2A and TP53 are mutated, the cascade of destabilization of the tumor cells progresses, and might indeed explain the worse survival of patients carrying both mutations. The worse survival in patients carrying TP53 and HRAS is in line with those of Zhang et al who showed a markedly increased number of tumors and tumor size in transgenic mice with TP53 and HRAS mutations [34]. The synergistic interaction and the resulting impairment of prognosis could be explained by the roles that both genes have in tumorigenesis.…”
Section: Discussionsupporting
confidence: 79%
“…When both CDKN2A and TP53 are mutated, the cascade of destabilization of the tumor cells progresses, and might indeed explain the worse survival of patients carrying both mutations. The worse survival in patients carrying TP53 and HRAS is in line with those of Zhang et al who showed a markedly increased number of tumors and tumor size in transgenic mice with TP53 and HRAS mutations [34]. The synergistic interaction and the resulting impairment of prognosis could be explained by the roles that both genes have in tumorigenesis.…”
Section: Discussionsupporting
confidence: 79%
“…The relationship between decreased invasiveness and increased Ras activity when farnesylation is inhibited is also unclear and may be due to the functional inhibition of H-Ras. H-Ras has been reported to increase invasiveness of various carcinomas (42, 43). Raponi et al found expression of RASGRP1 , a guanine nucleotide exchange factor (GEF) that activates Ras, predicted sensitivity to tipifarnib treatment in AML (44).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, inactivated TP53 and mutated c-Ha-RAS act synergistically in making cells vulnerable to chemically induced carcinogenesis in vitro and also in vivo [47, 48]. The ts p53 used in our work was shown to synergistically induce malignant transformation together with c-Ha-Ras in primary RECs [12].…”
Section: Discussionmentioning
confidence: 99%